Comparing the Personality Traits and Childbirth-related Beliefs of Two Groups of Women undergoing Vaginal Delivery and Cesarean Section - Hosain Khooban; Mohamad Reza Asadi Yoonesi (Mashhad University of Medical Sciences, 2021)
Background & aim: The excessive increase in the number of cesarean sections is one of the problems of health care in all societies, including Iran. This study aimed to compare two groups of women based on their preferred mode of delivery in terms of their personality traits and beliefs toward the mode of delivery in Iran. Methods: This comparative descriptive study was performed on 60 pregnant women in their last months of pregnancy, who decided for cesarean section or natural birth and were selected from doctors' offices and healthcare centers through cluster sampling technique in Birjand, Iran in 2107. Data were collected through the Big Five personality questionnaire, and two other questionnaires to measure religious attitudes and beliefs toward delivery. To analyze the data, independent t-test, and multivariate analysis of variance were employed using SPSS (version 16). Results: Considering the personality traits, the mean value of extraversion was significantly different between the two groups (p <0.05), meaning that women who preferred the natural birth were more extravert. Furthermore, there was a significant difference in terms of attitude towards mode of delivery between two groups and those who decided for the cesarean section had more positive attitude toward cesarean and negative attitude toward natural birth (p <0.001). Conclusion: Considering positive attitude of women toward cesarean section, it seems crucial that physicians, midwives, birth counselors, and the media design interventions focused on promotion of normal birth to change the misconceptions about cesarean section and to encourage mothers to undergo natural childbirth.